Motor function outcome in postnatal insult-related cerebral palsy - Fauzi, A.A.; Mustafah, N.M.; Zohdi, W.N. (2013)
Abstract INTRODUCTION: The Gross Motor Function Classification System (GMFCS) was developed to establish uniform communication between healthcare providers, patients, and the patients' families. It is also used to prognosticate the outcome of motor function. Based on previous reports, prognostication of ambulation status in cerebral palsy is based on the motor development curve, which shows a plateau at a certain known age. CASE REPORT: This report illustrates the case of a boy with spastic triplegic cerebral palsy secondary to postnatal insult at early childhood. The patient was noted to have tremendous progressive improvement in his GMFCS level beyond 7 years old: from level IV at 4 years old to level II at 9 years old. CONCLUSION: Prognostication of ambulation in cerebral palsy based on the motor development curve provides a basis for physicians to predict motor function outcome and plan appropriate intervention. This case report shows that other important factors need to be considered in the clinical evaluation before rendering the prognostication of motor function outcome, including environmental factors as well as the etiology of cerebral palsy, for which special consideration should be given in cases of postnatal insult-related cerebral palsy.